2023
DOI: 10.1039/d2nj03627d
|View full text |Cite
|
Sign up to set email alerts
|

Easy access to Ugi-derived isatin-peptoids and their potential as small-molecule anticancer agents

Abstract: The amide bond is one of the most important functional motifs in chemistry and biology due to its presence in countless biological structures and is of significant synthetic interest. Small-molecule...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Resourcefulness of the Ugi4CR and preliminary SAR studies [16] lead us to synthesize a third library of oxindole-derivatives, using trifluoroacetic acid (TFA), in mild reaction conditions, to afford the corresponding -acetoamide carboxamide isatin hybrids 8 from the 3-protected oxindole counterparts 5 and 7, in moderate to good yields (Scheme 4). The best yield was obtained when 3-protected oxindole derivatives 5 possess an aromatic or heterocyclic unit substituted in the 5-amide position of the oxindole ring.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Resourcefulness of the Ugi4CR and preliminary SAR studies [16] lead us to synthesize a third library of oxindole-derivatives, using trifluoroacetic acid (TFA), in mild reaction conditions, to afford the corresponding -acetoamide carboxamide isatin hybrids 8 from the 3-protected oxindole counterparts 5 and 7, in moderate to good yields (Scheme 4). The best yield was obtained when 3-protected oxindole derivatives 5 possess an aromatic or heterocyclic unit substituted in the 5-amide position of the oxindole ring.…”
Section: Methodsmentioning
confidence: 99%
“…Underlining sustainability and economically favored processes, a second family of acetoamide carboxamide oxindole derivatives 5 was obtained using the previously optimized Ugi4CR approach [16] (Scheme 2 and Figure 2). Taking into account the preliminary SAR studies reported for the first family of Ugi-derived isatin-peptoids, the second family was obtained using the 5-amino-1-benzyl-3,3-dimethoxyindolin-2-one [12] 1 and the benzyl isocyanide 4, as amine and isocyanide components, respectively.…”
Section: Synthesismentioning
confidence: 99%
See 3 more Smart Citations